2015
DOI: 10.1371/journal.pone.0117374
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Collectivism with Relationship Commitment, Passion, and Mate Preferences: Opposing Roles of Parental Influence and Family Allocentrism

Abstract: In collectivist cultures, families tend to be characterized by respect for parental authority and strong, interdependent ties. Do these aspects of collectivism exert countervailing pressures on mate choices and relationship quality? In the present research, we found that collectivism was associated with greater acceptance of parental influence over mate choice, thereby driving relationship commitment down (Studies 1 and 2), but collectivism was also associated with stronger family ties (referred to as family a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 75 publications
(121 reference statements)
2
39
0
Order By: Relevance
“…In similar way young adults in Singapore value the needs and the perspectives of their significant others or their social community (Chang, & Lee, 2012). This coincides with the past studies that revealed interdependent relationships has important consequences for allocentric individuals' psychological adjustment and health including children (e.g., Schaerfl, 2009), and impact on romantic relationship passion and commitment (Bejanyan, Marshall, & Ferenczi, 2015).…”
Section: The Construct Of Relationship Beliefs About Changesupporting
confidence: 90%
“…In similar way young adults in Singapore value the needs and the perspectives of their significant others or their social community (Chang, & Lee, 2012). This coincides with the past studies that revealed interdependent relationships has important consequences for allocentric individuals' psychological adjustment and health including children (e.g., Schaerfl, 2009), and impact on romantic relationship passion and commitment (Bejanyan, Marshall, & Ferenczi, 2015).…”
Section: The Construct Of Relationship Beliefs About Changesupporting
confidence: 90%
“…Complexity relates principally to differences in a number of areas, including family structure and composition and parenting styles based on racial, ethnic, and religious determinants. Challenges relate to dilemmas encountered by therapists in carrying out cross‐cultural parenting assessments given differences on how they construct the notion of ‘family,’ which guides their parenting styles (Bejanyan et al., ).…”
Section: Resultsmentioning
confidence: 99%
“…Several authors in the United Kingdom, United States, and Australia have pointed to complexities and challenges therapists face when working with families from CaLD backgrounds (Bejanyan, Marshall, & Ferenczi, 2015;Crippen & Brew, 2007;Sawrikar, 2009Sawrikar, , 2013Singh & Clarke, 2006). Complexity relates principally to differences in a number of areas, including family structure and composition and parenting styles based on racial, ethnic, and religious determinants.…”
Section: Familial and Parental Differences Between Familiesmentioning
confidence: 99%
“…This piece of research therefore adds to our knowledge of how to help young people to establish healthy romantic relationships, one of the principal developmental tasks of emerging adulthood, and does so by analysing the role played by family in this undertaking. Indeed, family continues to be a key development context for young people and influences their choice of romantic partner [54]. There are many young people who, in both Spain and many other Western countries, continue to live in the family home until well into their third decade of life.…”
Section: Discussionmentioning
confidence: 99%